Conceptualising Big Data within the Indonesian Trade Secrets Legal Framework - Moch. Marsa Taufiqurrohman; Tarsisius Murwadji; Helza Nova Lita (Jurnal Kajian Pembaruan Hukum, 2025)
Big data phenomenon has transformed global digital economy landscape, yet unclear legal status in Indonesia creates protection gaps that disadvantage technology innovators and business actors. This legal uncertainty has become increasingly urgent as Indonesia's digital economy accelerates post-pandemic, with data-driven startups and established businesses facing immediate risks from inadequate intellectual property protection in competitive global markets. Insufficient legal framework to protect big data as intellectual assets potentially hinders technology investment and knowledge transfer in digital transformation era. This article, employing a combination of normative juridical research and comparative analysis methodology, aims to establish big data conceptualization as trade secret protection objects within Indonesia's intellectual property legal framework. This article argues that big data characteristics encompassing information secrecy, substantial economic value, and adequate protection efforts, fulfill trade secret requirements as regulated in Article 3 of Law Number 30 Year 2000 concerning Trade Secrets. Analysis of big data protection practices in European Union through Trade Secrets Directive and comparative study with United States and China jurisprudence demonstrates legal approach convergence enabling adaptation within Indonesian legal system. This ultimately meets business information protection elements based on Article 2 of Law Number 30 Year 2000 concerning Trade Secrets, rendering big data protection practices as trade secrets legally justifiable. Article concludes by suggesting that policymakers should establish adequate frameworks and regulations to accommodate big data protection as trade secrets in digital markets. This would promote sustainable technology innovation and protect Indonesian digital business actors' interests in global competition.